Effects of interactions between microorganisms and lipids on inferior volatile compound production during cold storage of grouper (Epinephelus coioides) - Yuanming Chu; Jinfeng Wang; Jing Xie (Food Chemistry: X)
The interaction between microorganisms, proteins, and lipids plays a critical role in the odor production of fish. To explore the specific impact of the interaction between lipids and microorganisms on the overall odor of grouper, this study excluded the influence of proteins and assessed lipid (POV and TBARS) and microbial characteristics (biofilm mass and ATP content) in lipid solutions. The Results showed that microbial growth and lipid oxidation mutually promote each other. Lipidomics analysis identified 44 differential lipids, and microbial diversity analysis pinpointed five key microorganisms (Carnobacterium, Pseudomonas, Gluconacetobacter, Vagococcus, and Shewanella). Furthermore, 20 key volatile compounds (VOCs) related to odor changes in the grouper lipid solution were identified using HS-SPME-GC–MS. Correlation network analysis revealed potential microbial and lipid contributions to VOC categories, including alcohols, aldehydes, ketones, and nitrogen- and sulfur-containing compounds. This study provides new insights into the roles of microorganisms and lipids in flavor formation, offering valuable knowledge for improving seafood quality control.